2021
DOI: 10.1016/j.lrr.2021.100284
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with double/triple expressor diffuse large B-cell lymphoma (DLBCL) treated with R-DA-EPOCH/R-CHOP: A single-center experience.

Abstract: In Pakistan 76.4% of all NHLs to be diagnosed as DLBCLs. The survival of R-CHOP is better compared to the DA-REPOCH treatment regimen. A prospective follow-up study was conducted with 113 patients to study the outcomes of treatment. Multivariable cox-proportional hazard model was used to estimate the hazard ratios in patients receiving these treatment regimens considering p-value ≤0.05 significant. The survival rate among double/triple expressor lymphoma patients received R-DA-EPOCH was 82.8%, and 83.3% receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Still, these data are based on younger and smaller series of patients [9,10]. Accordingly, limited reports have already been published comparing the R-CHOP and R-DA-EPOCH in the DEL patient population, among which is a study by Devi and colleagues [22] that included 113 patients and a multicentre study of 90 patients in the USA [23]. Both studies actually disclosed no differences in survival among the two protocols applied.…”
Section: Discussionmentioning
confidence: 99%
“…Still, these data are based on younger and smaller series of patients [9,10]. Accordingly, limited reports have already been published comparing the R-CHOP and R-DA-EPOCH in the DEL patient population, among which is a study by Devi and colleagues [22] that included 113 patients and a multicentre study of 90 patients in the USA [23]. Both studies actually disclosed no differences in survival among the two protocols applied.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, a small study from the same year [28] showed a favorable treatment outcome with R-EPOCH in comparison with R-CHOP in DEL DLBCL patients. In the following years, the number of researches that do not favor therapy intensification for patients with DEL [29][30][31] notably outnumbered those who do favor intensification [32]. Systematic review and meta-analysis by Hwang et al [33], that included 7054 patients from 41 studies, confirmed that CR rate is significantly lower in newly diagnosed DEL than non-DEL DLBCL patients.…”
Section: Clinical Implication Of Double Expressor Lymphomas and Treat...mentioning
confidence: 99%
“…Devi и соавт. [8] показали, что при медиане наблюдения 2 года медианы ОВ и ВБП в группе больных с ДВККЛ (DHL/THL), получавших терапию R-EPOCH, были аналогичны таковым в группе пациентов с этим же вариантом лимфопролиферативного заболевания, которым проводилось лечение в режиме R-CHOP, составив 13,8 мес против 14,2 мес и 10,5 мес против 10,6 мес соответственно. При этом авторы не отметили увеличения токсичности в случае применения режима R-EPOCH.…”
Section: Introductionunclassified